Câu 41: trang 23 - sgk toán 7 tập 1
Tính :
a. $(1+\frac{2}{3}-\frac{1}{4}).(\frac{4}{5}-\frac{3}{4})^{2}$
b. $2:(\frac{1}{2}-\frac{2}{3})^{3}$
Bài Làm:
a, $(1+\frac{2}{3}-\frac{1}{4}).(\frac{4}{5}-\frac{3}{4})^{2}$
= $(\frac{12+8-3}{12}).(\frac{16-15}{20})^{2}$
= $(\frac{17}{12}).(\frac{1}{20})^{2}$
= $(\frac{17}{12}).\frac{1}{400}$
= $\frac{17}{4800}$
Vậy $(1+\frac{2}{3}-\frac{1}{4}).(\frac{4}{5}-\frac{3}{4})^{2}=\frac{17}{4800}$
b. $2:(\frac{1}{2}-\frac{2}{3})^{3}$
= $2:(\frac{3-4}{6})^{3}$
= $2:(\frac{-1}{6})^{3}$
= $2:\frac{-1}{216}$
= $2.-216=-432$
Vậy $2:(\frac{1}{2}-\frac{2}{3})^{3}=-432$